An expanded nuclear phylogenomic PCR toolkit for Sapindales1. (7th December 2016) - Collins, Elizabeth S.; Gostel, Morgan R.; Weeks, Andrea
Abstract : Premise of the study: We tested PCR amplification of 91 low‐copy nuclear gene loci in taxa from Sapindales using primers developed for Bursera simaruba (Burseraceae). Methods and Results: Cross‐amplification of these markers among 10 taxa tested was related to their phylogenetic distance from B. simaruba . On average, each Sapindalean taxon yielded product for 53 gene regions (range: 16–90). Arabidopsis thaliana (Brassicales), by contrast, yielded product for two. Single representatives of Anacardiaceae and Rutacaeae yielded 34 and 26 products, respectively. Twenty‐six primer pairs worked for all Burseraceae species tested if highly divergent Aucoumea klaineana is excluded, and eight of these amplified product in every Sapindalean taxon. Conclusions: Our study demonstrates that customized primers for Bursera can amplify product in a range of Sapindalean taxa. This collection of primer pairs, therefore, is a valuable addition to the toolkit for nuclear phylogenomic analyses of Sapindales and warrants further investigation.